2017
DOI: 10.1007/s00246-016-1565-6
|View full text |Cite|
|
Sign up to set email alerts
|

Decreased Diastolic Ventricular Kinetic Energy in Young Patients with Fontan Circulation Demonstrated by Four-Dimensional Cardiac Magnetic Resonance Imaging

Abstract: Four-dimensional (4D) flow magnetic resonance imaging (MRI) enables quantification of kinetic energy (KE) in intraventricular blood flow. This provides a novel way to understand the cardiovascular physiology of the Fontan circulation. In this study, we aimed to quantify the KE in functional single ventricles. 4D flow MRI was acquired in eleven patients with Fontan circulation (median age 12 years, range 3–29) and eight healthy volunteers (median age 26 years, range 23–36). Follow-up MRI after surgical or percu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…Since kinetic energy reflects ventricular performance, it could potentially be a novel and advanced method for evaluation of the cardiac function 19. Intracardiac kinetic energy has been shown to be abnormal in patients with ToF, Fontan circulation, mitral regurgitation and heart failure 20…”
Section: D-flow Cmrmentioning
confidence: 99%
“…Since kinetic energy reflects ventricular performance, it could potentially be a novel and advanced method for evaluation of the cardiac function 19. Intracardiac kinetic energy has been shown to be abnormal in patients with ToF, Fontan circulation, mitral regurgitation and heart failure 20…”
Section: D-flow Cmrmentioning
confidence: 99%
“…In this latter study, the increase of kinetic energy is explained by a 50% decrease of the combined crosssectional area of the SVC and IVC compared with the PAs. 95 It should be noted that kinetic energy is only part of the energy equation (Appendix I in the online-only Data Supplement) and does not represent total energy loss. Although 4D flow MRI is a promising noninvasive technique that can be easily implemented in clinical care, spatial resolution (ie, the size of the voxels in mm 3 ) is a major issue because this has been shown to be the limiting factor in accurately calculating energy loss (Appendix I in the online-only Data Supplement).…”
Section: D Flow Mri Studiesmentioning
confidence: 99%
“…For example, one study found decreased diastolic kinetic energy (KE) in patients with Fontan circulation compared with controls. 8 However, further study is needed because multiple studies have shown that KE is often higher in the ventricle or atria of patients with heart disease than in healthy controls.…”
mentioning
confidence: 99%